2022
DOI: 10.3390/brainsci12111505
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Inter-Hemispheric Functional Connectivity during Resting State in Female Patients with Migraine

Abstract: The application of voxel-mirrored homotopic connectivity (VMHC) analysis to study the central mechanism of migraine has been limited. Furthermore, little is known about inter-hemispheric functional connectivity (FC) alterations during resting state in female patients with migraine. This study aimed to investigate potential interictal VMHC impairments in migraine without aura (MwoA) patients and the relationship between connectivity alterations and clinical parameters. Resting-state functional magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Brain imaging studies on pain induction suggested that the primary somatosensory (S1), secondary somatosensory (S2), insula, prefrontal cortices and other brain regions could be regarded "pain matrix", whose functions were abnormal in the process of pain induction [37], which was consistent with our results. Dysfunctions of DMN and most regions of the sensorimotor circuit were involved in the neural mechanism of non-menstrual MwoA in female [38]. In this study, we found that DMN and sensorimotor circuit had a cross effect on the regulation and processing of pain, which could affect sensory, emotional and cognitive processing at multiple levels.…”
Section: Characteristics Of Changes Of Brain Spontaneous Activity And...mentioning
confidence: 56%
“…Brain imaging studies on pain induction suggested that the primary somatosensory (S1), secondary somatosensory (S2), insula, prefrontal cortices and other brain regions could be regarded "pain matrix", whose functions were abnormal in the process of pain induction [37], which was consistent with our results. Dysfunctions of DMN and most regions of the sensorimotor circuit were involved in the neural mechanism of non-menstrual MwoA in female [38]. In this study, we found that DMN and sensorimotor circuit had a cross effect on the regulation and processing of pain, which could affect sensory, emotional and cognitive processing at multiple levels.…”
Section: Characteristics Of Changes Of Brain Spontaneous Activity And...mentioning
confidence: 56%
“…Brain imaging studies on pain induction suggested that the primary somatosensory (S1), secondary somatosensory (S2), insula, prefrontal cortices and other brain regions could be regarded "pain matrix", whose functions were abnormal in the process of pain induction [21], which was consistent with our results. Dysfunctions of DMN and most regions of the sensorimotor circuit were involved in the neural mechanism of non-menstrual MwoA in female [22]. In this study, we found that DMN and sensorimotor circuit had a cross effect on the regulation and processing of pain, which could affect sensory, emotional and cognitive processing at multiple levels.…”
Section: Correlation Analysis Between Alff or DC Values And Sf-mpq Or...mentioning
confidence: 56%
“…We filtered one DC study (Ke et al, 2020) and two VMHC studies (Cao et al, 2022; Zhang et al, 2022). Combined with the existing included studies on ALFF, fALFF, and ReHo, we carried out AES‐SDM, ALE, and MKDA analysis again.…”
Section: Resultsmentioning
confidence: 99%